Narrative therapy and the autism spectrum: A model for clinicians. Issue 2 (1st May 2021) - Monteiro, Marilyn J
Narrative therapy practices have a long history of application to a wide range of mental health conditions. This paper discusses a novel narrative approach specific to autism and the application of narrative therapy constructs for clinicians working with families who have a member with a diagnosis of autism spectrum brain style differences. The author introduces a visual framework and descriptive language as a reference point to think and talk about autism within the context of narrative family therapy. This framework guides clinicians toward supporting an individualized narrative of the pattern of strengths and differences that are part of the autism spectrum brain style. The narrative approach outlined in this paper provides the entry point for clinicians to guide families toward the development of strength-based narratives that foster connections and resiliency within the family. A narrative therapy model is introduced with three key features highlighted: structuring the session to accommodate for autism spectrum brain style differences, using descriptive language to support the development of alternative narratives, and highlighting key narrative shifts taken from family therapy sessions. Readers are provided with a case study that illustrates the use of narrative therapy structures when working with this unique population of families.